Playing the Female Fool: Metamorphoses of the Fool from Fireworks to The Bloody Chamber (Altre Modernità, 2020)
This article looks at the representation of the fool in the first two short story collections by Angela Carter, namely Fireworks (1974) and The Bloody Chamber (1979). Its central argument is that the quintessentially subversive presence of the fool is theorized and developed in Carter’s earlier short stories, in a way that leads to a radical shift in her poetics and in the reader’s perception of her writing. In fact, a path of evolution of this figure is traced in Carter’s female characters in her first two short story collections, outlining how the female fool develops from an individualist and vengeful rebel in Fireworks to a more socially constructive dissident in The Bloody Chamber. The female fool is seen as an experimental symbol of female subversion which is deeply intertwined with Carter’s self-awareness as a feminist writer, developing alongside her first conceptualization of this figure. The article starts with an outline of the three fool figures which exemplify the female fool’s evolution from the first to the second short story collection; it then proceeds to analyze the short stories that foreground female fool figures. The last section focuses on the figure of the healing female fool, whose transformative potential eventually brings about long-lasting and constructive effects.